ANALISIS IMPLEMENTASI MODEL PEMBELAJARAN MULTIPLE INTELLIGENCE DALAM PEMBELAJARAN PKN MATERI KEANEKARAGAMAN EKONOMI PADA SISWA KELAS VI SDN 10 TOHO - Endang, Asteria; Cahyani, Christina Wahyu; Serani, Gabriel; Sulistyarini, Sulistyarini (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
The aim of this study is to analyze the implementation of the Multiple Intelligences (MI) learning model in designing lesson plans, conducting learning activities, and examining student responses to the learning process. This study employed a descriptive qualitative method, involving the analysis of lesson plan documents, classroom observations, and interviews with students. The respondents were sixth-grade students, and the data were analyzed using a narrative technique. The results indicate that the Multiple Intelligences (MI) learning model is effective in enhancing students' understanding of abstract concepts related to social, cultural, and economic diversity, as well as in developing students’ intelligence potentials through visual, auditory, and kinesthetic-based activities. These findings contribute to the development of more inclusive and engaging learning methods for elementary school students.